Public Services Based on Workforce Training Management (Case Study at the Department of Cooperatives, Small and Medium Enterprises, Manpower, and Transmigration of Yogyakarta City) - Sopyan, Ence; Apriza , Tiyas (International Journal of Public Administration and Policy, 2025)
This study examines how training management is implemented by the Workforce Productivity Development and Training Section for Workers at the Cooperatives, Small and Medium Enterprises, Manpower, and Transmigration Service in the city of Yogyakarta. This study uses interview and documentation data collection methods. The training management implemented by the Workforce Productivity Development and Training Section is in accordance with theoretical management principles. Among them are training analysis according to needs, determination of the required training curriculum, determination of methods, media, and instructors. Not only that, in managing training for workers, training supervision is implemented by the monitoring team owned by this Section and training assessment as a reference for issuing training participant certification.